A prospective study of colonoscopic examination at al-kindy teaching hospital - Hassan, Riyadh Mohammad (AL-Kindy College Medical Journal, 2010)
Background: Fiber-optic endoscopy is an important investigation of the large intestine, whether or not the radiologist (barium enema) has discovered a lesion in the bowel. Colonoscopy affords a unique opportunity to direct visualization of entire colonic mucosa. At the same time, the physician can obtain biopsy specimens, remove polyps, and decompress volvuli. Most experienced endoscopists and well prepared patients can reach the cecum in over 90% of patients. If colonoscopy is properly performed, it has a low risk of complications, such as perforation and bleeding. Methods: A total of 70 consecutive patients admitted to Endoscopy department at Al-Kindy Teaching hospital from September- 2008 to July-2009. Bowel preparation was achieved with Polyethylene glycol lavage solution and 165 cm Pentax colonoscope EC_3385FK 4.2 was used in all cases. All patients were not sedated or given any other medication Results:Seventy colonoscopies were performed in this study. Forty of them were male and the rest were female. The mean age was 42 years ranging from 4 years to 85 years. The most common indication for colonoscopy was rectal bleeding (44%) Polyethylene glycol lavage solution was used in all patients for bowel preparation. All patients did not receive premedications. Complete colonoscopy examination was done in (12.8%) of patients, the most common cause of incomplete examination was poor bowel preparation (50%). No complications were reported. Conclusions: Rectal bleeding was the most common indication for colonoscopy. Poor bowel preparation was the main cause of incomplete colonoscopy